The Effectiveness of Multimodal Text to Enhance Attention Span in Students’ Reading Performance in SMK Andalusia Wonosobo - Ratna Wulandari; Arif Widyantoro (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2026)
The objective of this study is to assess the effectiveness of multimodal texts in enhancing students' attention span in reading performance. This study involves 32 students at SMK Andalusia Wonosobo. This research uses a quantitative method with an experimental research design and data collection techniques in the form of tests, documentation, and hypothesis testing. The results of this research show that the experimental group achieved more effective learning outcomes, as well as showing a contrasting difference with the control class. The T-test result was 0.039. The hypothesis was accepted because T-test was less than 0.05. Moreover, the coefficient of determination value of 0.502 (50.2%) can indicate that multimodal text is sufficiently effective in enhancing students' attention span during reading performance.